Estrategias de motivación en clases virtuales y el aprendizaje de la matemática en los niños de cinco años de la Institución Educativa Inicial N° 602, San Juan 2021 - Rodriguez Gonzales, Brenda Verusca (2023)
In the study carried out, the main purpose was to determine if the motivation strategies in virtual classes are related to learning in the area of mathematics in infants at five years of age from the initial educational center No. 602 San Juan-2021. The type of study has been quantitative, relational, non-experimental, which allowed measuring the relationship between motivation strategies and learning in the area of mathematics in infants of the aforementioned educational center. The population that was considered was 40 five-year-old children, and as a sample to be considered adequate, the same number of children was taken. To collect the data as a technique in the first variable (x), and in the second variable (y) observation was used; As an instrument, the previously validated observation guide was applied to both variables. Finally, it is concluded in the investigation that there is an important association in the motivation strategies in virtual classes and the second variable, the learning of mathematics in the infants of the initial educational center N° 602 San Juan-2021.